Academic policy for establishing new junior high schools in South Tangerang City - Mustofa Kamil; Neneng Nurjanah; Muhammad Yus Firdaus; Bambang Mardi Sentosa; Purnomo Purnomo; Cucu Sukmana (Inovasi Kurikulum, 2024)
This study explores the academic policy regarding establishing new Junior High Schools (SMP) in South Tangerang City in response to the rising number of Elementary School (SD) graduates and the limited availability of secondary education facilities. Using a theoretical and quantitative approach, the research applies the "Social Demand Approach" planning model to identify the need for new schools. Findings reveal a significant imbalance between the number of SD and SMP, particularly in Setu, North Serpong, Pondok Aren, and Ciputat sub-districts, highlighting an urgent need for new school units (USB) and classrooms (RKB) to ensure equitable access to quality education. The analysis is supported by geographic and demographic data, considering essential variables such as student group sizes (rombel). Therefore, the policy for establishing new schools in South Tangerang City must be implemented promptly to address primary and secondary education challenges, ensuring adequate facilities for the growing student population. The research emphasizes the importance of addressing educational infrastructure needs to support student's educational progress and highlights the critical role of geographic information systems (GIS) in mapping school locations and planning future school development.   Abstrak Penelitian ini mengeksplorasi kebijakan akademik terkait pendirian Sekolah Menengah Pertama (SMP) baru di Kota Tangerang Selatan sebagai respons terhadap meningkatnya jumlah lulusan Sekolah Dasar (SD) dan terbatasnya ketersediaan fasilitas pendidikan menengah. Dengan menggunakan pendekatan teoritis dan kuantitatif, penelitian ini menerapkan model perencanaan "Social Demand Approach" untuk mengidentifikasi kebutuhan akan sekolah baru. Temuan menunjukkan ketidakseimbangan yang signifikan antara jumlah SD dan SMP, khususnya di kecamatan Setu, Serpong Utara, Pondok Aren, dan Ciputat, menyoroti kebutuhan mendesak akan unit sekolah baru (USB) dan ruang kelas (RKB) untuk memastikan akses yang merata terhadap pendidikan berkualitas. Analisis didukung oleh data geografis dan demografis, mempertimbangkan variabel penting seperti ukuran kelompok peserta didik (rombel). Oleh karena itu, kebijakan pendirian sekolah baru di Kota Tangerang Selatan harus dilaksanakan segera untuk mengatasi tantangan dalam pendidikan dasar dan menengah, serta memastikan fasilitas yang memadai bagi populasi peserta didik yang berkembang. Penelitian ini menekankan pentingnya pemenuhan kebutuhan infrastruktur pendidikan untuk mendukung kemajuan peserta didik. Sistem informasi geografis (GIS) memainkan peran penting dalam pemetaan lokasi sekolah dan perencanaan pengembangan pendidikan di masa depan. Kata Kunci: kebijakan pendidikan; kelompok belajar pendirian SMP; social demand approach